2005
DOI: 10.1103/physrevb.71.033302
|View full text |Cite
|
Sign up to set email alerts
|

Above room temperature ferromagnetism in Mn-ion implanted Si

Abstract: Above room temperature ferromagnetic behavior is achieved in Si through Mn ion implantation. Threehundred-keV Mn + ions were implanted to 0.1% and 0.8% peak atomic concentrations, yielding a saturation magnetization of 0.3 emu/ g at 300 K for the highest concentration as measured using a SQUID magnetometer. The saturation magnetization increased by ϳ2ϫ after annealing at 800°C for 5 min. The Curie temperature for all samples was found to be greater than 400 K. A significant difference in the temperature-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
159
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(172 citation statements)
references
References 29 publications
4
159
3
2
Order By: Relevance
“…As previously observed for Mn-containing samples [16,17] and in accordance with the literature [34,35], the MFM measurements for the Co-free Si and Ge films (both amorphous and annealed up to crystallization temperature) did not exhibit any magnetic contrast. When annealed at high temperatures, the XRD results indicated that non-magnetic phases were present in the films containing Co.…”
Section: Resultssupporting
confidence: 71%
“…As previously observed for Mn-containing samples [16,17] and in accordance with the literature [34,35], the MFM measurements for the Co-free Si and Ge films (both amorphous and annealed up to crystallization temperature) did not exhibit any magnetic contrast. When annealed at high temperatures, the XRD results indicated that non-magnetic phases were present in the films containing Co.…”
Section: Resultssupporting
confidence: 71%
“…Diluted magnetic semiconductor (DMS) can serve as an avenue to utilize both charge and spin functions of electrons for various applications [1]. Many group IV [2], III-V [3], and II-VI [3] DMS materials have been obtained by doping magnetic impurities into semiconductors. Nevertheless, most of them have a low Curie temperature (T C ), which limits their practical applications.…”
mentioning
confidence: 99%
“…The interfacial quality may have a strong effect on the injection efficiency so epitaxial growth will be necessary. Materials such as dilute magnetic semiconductors Mn-doped Si [68], Mn-doped chalcopyrites [69][70][71][72][73] or the 'pure' ferromagnetic semiconductor EuO [74] have all been suggested, but none as yet have been demonstrated as spin injectors for Si. It should be noted that while their intrinsic compounds are indeed semiconductors, owing to the carrier-mediated nature of the ferromagnetism, it is seen only in highly (i.e.…”
Section: Spins In Siliconmentioning
confidence: 99%